Perceived Intrusiveness and Digital Audience : An Empirical Approach - Vijayakumar, Gajenderan; Rahiman, Habeeb Ur; Nawaz, Nishad; Sriranga Prasad, N. V. (Indian Journal of Marketing, 2024)
Purpose : Since some advertising set-ups are considered obtrusive by consumers, the way that they perceive advertising has become more and more sophisticated. Finding consumer knowledge of and reaction to different types of online audience intrusiveness in digital media ads was the aim of this study. Methodology : The study administered a purposive approach to investigate intrusive advertisements and consumer awareness and responses. The sample was collected from 381 samples from Bahrain and India through a structured questionnaire. The results were analyzed by inferring a structural equation model, regression, and descriptive statistics through Smart PLS and SPSS. Findings : The results indicated that consumers are unaware of privacy invasion arising from digital marketing advertisement technology like facial recognition, eye tracking, and GPS tracking; however, they are aware of privacy invasion occurring through social media. The results explored that online ads are considered intrusive, and consumers deliberately do not pay attention to the ads on social networking services. Practical Implications : The advertisers and practitioners carefully assess which internet advertising type is to be used based on the goal of their campaign. In the days of the information age, it is essential to evaluate consumers’ preferences and choices and provide them with more relevant communications by owing to knowledge about users’ navigational behaviors. Originality : The study contributed to the field of digital media advertisement by linking perceived consumer instructiveness. The outcome of the study proposed a framework for future research by focusing on the research gap and key findings in this domain.